Resources for sports engineering education - Allen, T.; Goff, J. E. (Sports Engineering, 2018)
This paper serves as a resource guide for Sports Engineering educators. The paper covers key topics in Sports Engineering, including ball impact, friction, safety and materials. A variety of resource types are presented to reflect modern methods of learning and searching for information, including textbooks, research and review papers, websites and videos. The field could benefit from more resources specifically designated for teaching Sports Engineering, particularly textbooks.